Has long‐distance flight ability been maintained by pigeons in highly insular habitats?. (27th November 2022) - Tsujimoto, Daichi; Ando, Haruko; Suzuki, Hajime; Horikoshi, Kazuo; Nakajima, Nobuyoshi; Suyama, Yoshihisa; Matsuo, Ayumi; Fujii, Chieko; Isagi, Yuji
Abstract: Aim: A reduction in dispersal ability has been thought to be a general trend for island land birds. However, recent studies have indicated that long‐distance dispersal among island habitats may be maintained in island pigeon populations. Here, we investigated whether pigeons could maintain their long‐distance dispersal ability to move among islands within the archipelago, even in highly insular conditions, by comparing two subspecies of Japanese wood pigeon distributed on islands with different levels of insularity. Location: The Ogasawara, Izu and Nansei Islands in the north‐western Pacific Ocean. Taxon: Japanese wood pigeon ( Columba janthina ). Methods: We compared the hand‐wing index related to dispersal potential between the two subspecies: C. j. janthina and C. j. nitens . We performed phylogenetic analyses with likelihood and Bayesian frameworks and estimated population genetic structure using the principal component analyses and individual admixture analyses based on the genotype likelihood of MIG‐seq SNPs. We calculated divergence times of the two subspecies using Bayesian and PSMC models for MIG‐seq SNPs and whole genome data, respectively. Results: C. j. nitens had a wing shape that was better suited for long‐distance flight than that of C. j. janthina . Both subspecies maintained sufficient gene flow among the islands within their habitat archipelagos, with no evidence of isolation by distance. The divergence time of the two subspecies was 0.67 (95%CI: 0.33–0.97) million years ago, which was sufficient to reduce dispersiveness compared to other cases of island land birds. Main Conclusion: Long‐distance flight can be maintained under highly insular conditions despite long‐term isolation from the ancestral populations. This indicates that the strategy of maintaining dispersal ability may also be possible in island systems, where organisms have repeatedly and globally shown reduced dispersal ability. Although further studies are required to reveal its evolutionary processes, our study provides an exceptional case for island birds' biogeography.